Vitamin Riboflavin production by two locally isolated yeast isolates and the effect of temperature and pH on their productivity - اليــن سركو; ميساء يازجي; نسرين نقشو (Latakia University Journal -Biological Sciences Series, 2023)
In this study, a group of yeasts were isolated from different natural sources, then they were purified and tested for their ability to produce the vitamin Riboflavin. The optimum temperature and pH to produce the largest amount of the vitamin were determined. 21 pure yeast isolates were obtained from different sources which they were able to produce riboflavin in a synthetic production medium. The results showed that two isolates of these yeasts superior in producing the largest amount of vitamin. The strains were identified by using the Carbohydrate fermentation method in the API strips (test kit), it turned out that they were: Candida famata and Candida guilliermondii. The ability of these two isolates to produce riboflavin differed according to the different conditions of temperature and pH applied in the experiments. It was found that conditions of 30 ° C and pH = 6 were optimal to give the largest amount of vitamin. The isolate C. guilliermondii was the best as it gave an amount of vitamin amounted to 172.24 g / 50 ml production medium under these conditions. Compared to the isolate C.famata, which produced an amount estimated at 57.84 g/50 ml production medium under the same conditions. whereas the amount of produced vitamin decreased to 53.84 µg and 0.24 µg for C.gulliermondii and C.famata, respectively, when the applied conditions were 30°C and pH=4.5. On the other hand, it was found that the conditions of temperature 35 ° C and pH = 7 were not suitable for producing vitamin by both isolates.